The Rise of Digital Literacy in Business Communication: A Bibliometric Analysis - Lisda Ariani Simabur (PT. Sangadji Media Publishing, 2025)
This study provides a comprehensive bibliometric analysis of the intersection between digital literacy and business communication, aiming to map the intellectual structure, thematic evolution, and research gaps within this emerging domain. Using data extracted from the Scopus database, a total of 13,126 documents were analyzed through country collaboration networks, keyword co-occurrence visualization, and subject area distribution. The findings reveal that research in this field is globally distributed yet dominated by contributions from developed countries. The subject area analysis demonstrates a strong interdisciplinary orientation, with the Social Sciences and Business, Management, and Accounting fields contributing the majority of publications. Keyword mapping indicates three major thematic clusters: digital literacy in organizational and technological contexts, socio-demographic and health-related dimensions, and external communication functions such as public relations and reputation management. Despite the large body of literature, only six documents were identified as directly addressing both digital literacy and business communication simultaneously, highlighting a significant research gap. This study underscores the need for a more integrated theoretical and empirical approach to understanding how digital literacy shapes communication effectiveness, organizational adaptation, and strategic engagement in digital business environments.